Mga kaisipan ni Balagtas sa kabataan at moralidad - Abueg, Efren Reyes (Animo Repository, 1995)
The Commission of the Filipino Language and the Manila City government cited four La Salle faculty members for their efforts in the development of the Filipino language. The awarding ceremonies were held in celebration of the 207th birth anniversary of Francisco Balagtas. The theme of the Araw ni Balagtas '95 was "Mga Kaisipan ni Balagtas sa Kabataan at Moralidad".